Infection Control and Prevention: A Review of Hospital-Acquired Infections and the Economic Implications - Reed, Deoine (the Academic Division of Ochsner Clinic Foundation, 2009)
The Centers for Disease Control and Prevention estimates that 2 million patients suffer from hospital-acquired infections every year and nearly 100,000 of them die. Most of these medical errors are preventable. Hospital-acquired infections result in up to $4.5 billion in additional healthcare expenses annually. The U.S. government has responded to this financial loss by focusing on healthcare quality report cards and by taking strong action to curb healthcare spending. The Medicare Program has proposed changes to the Hospital Inpatient Prospective Payment System and Fiscal Year Rates: Proposed Rule CMS 1488-P-Healthcare-associated infection. Payment will be linked to performance. Under the new rule, payment will be withheld from hospitals for care associated with treating certain catheter-associated urinary tract infections, vascular catheter-associated infections, and mediastinitis after coronary artery bypass graft surgery. Infection-prevention strategies are essential. In the healthcare setting, the infection control department is categorized as non-revenue-producing. Funds dedicated to resources such as staff, educational programs, and prevention measures are vastly limited. Hospital leaders will need to balance the upfront cost needed to prevent hospital-related infections with the non-reimbursed expense accrued secondary to potentially preventable infections. The purpose of this paper is to present case studies and cost analysis of hospital-acquired infections and present strategies that reduce infections and cost.